Modified Anatomical Reconstruction of the Medial Collateral Ligament With Tibial Sling Bone Tunnels and Double-Bundle Semitendinosus Tendon - Sergio Marinho de Gusmão Canuto, M.D.; José Leonardo Rocha de Faria, M.D., M.Sc., Ph.D.; Igor Farias de Araújo, M.D.; Pedro Enio Feitosa Bezerra, M.D.; João Henrique da Silva Araújo, M.D.; Diego Ariel de Lima, M.D., Ph.D.; Diego Escudeiro de Oliveira, M.D., M.Sc.; Bernardo Garcia Barroso, M.D.; Arthur Macedo de Gusmão Canuto, M.S.; Pedro Baches Jorge, M.D., Ph.D.; Vitor Barion Castro de Pádua, M.D., Ph.D.; Camilo Partezani Helito, M.D., Ph.D. (Arthroscopy Techniques)
This article describes a modification of an surgical technique for the anatomical reconstruction of the superficial medial collateral ligament (MCL) of the knee using a semitendinosus tendon graft in a minimally invasive approach. The MCL often is the site of severe injuries, which can result in long-term complications such as instability. The detailed surgical technique begins with an examination under anesthesia and diagnostic arthroscopy for accurate injury assessment. The semitendinosus tendon is used as a graft and fixed in the tibial communicating tunnels, with interference screw fixation only on the femur, restoring the integrity of the MCL. The postoperative protocol involves a careful rehabilitation process, including weight-bearing restriction and gradual return to sports activities. This technique offers advantages such as increased graft strength and lower surgical morbidity, making it a viable option for patients with anteromedial instabilities and grade III MCL injuries, especially when there are concomitant anterior cruciate ligament injuries. The anatomical reconstruction of the MCL with a double bundle and semitendinosus tendon graft is a promising technique that continues to be refined and studied in the quest for improved long-term outcomes in knee stability.